Controllability and minimum energy control of fractional neutral delay system⁎. Issue 1 (2018) - Priya, B. Ganesh; Muthukumar, P.
Abstract: In this paper, we consider a class of time invariant control system governed by the neutral delay differential equation of fractional order 1 < α ≤ 2. Necessary and sufficient conditions for the controllability of linear fractional neutral system is derived. The existence of solution and controllability for the proposed nonlinear system is obtained by using the successive approximation technique. Also, the minimum energy control problem of corresponding linear positive system is stated and proved by using the Grammian matrix approach. Finally two numerical examples are substantiated to illustrate the proposed theory.